2004
DOI: 10.1183/09031936.04.00039004
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and cigarette smoking

Abstract: In most developed countries y25% of adults with asthma are current cigarette smokers. Asthma and active cigarette smoking interact to cause more severe symptoms, accelerated decline in lung function, and impaired short-term therapeutic response to corticosteroids.Cigarette smoking may modify inflammation that is associated with asthma, although there is limited published data on airway pathology in smokers with asthma. To date, the evidence points towards a combination of both heightened and suppressed inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
276
5
24

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(313 citation statements)
references
References 155 publications
(193 reference statements)
8
276
5
24
Order By: Relevance
“…To the best of the current authors' knowledge, this is the first study to report on this matter, as most previous studies addressing atopy versus smoking have focused on the tobacco-induced increased risk of developing atopy and asthma [21,22] and on the increased severity, inflammation and progress of atopic diseases, such as asthma in smokers [23][24][25].…”
Section: Discussionmentioning
confidence: 97%
“…To the best of the current authors' knowledge, this is the first study to report on this matter, as most previous studies addressing atopy versus smoking have focused on the tobacco-induced increased risk of developing atopy and asthma [21,22] and on the increased severity, inflammation and progress of atopic diseases, such as asthma in smokers [23][24][25].…”
Section: Discussionmentioning
confidence: 97%
“…Little is known regarding the influence of smoking on the bronchial inflammatory response in asthma. Only few data are available on airway pathology in smoking asthmatics, as reviewed by THOMSON et al [6]. The main findings are reduced eosinophils in both induced sputum and peripheral blood, while neutrophils are increased in induced sputum samples.…”
mentioning
confidence: 99%
“…(3) Prevalence of active and passive smoking in a population of patients with asthma* function characteristics, as well as data related to asthma profile and smoking status, are presented in Table 1.…”
mentioning
confidence: 99%
“…Although there is still little information specifically regarding asthma patients who smoke, one group of authors reported that the prevalence of active smokers among asthma patients can range from 17% to 35%. (3) Early detection of active or passive smoking in asthma patients is essential so that smoking cessation programs can be offered to them. Such programs, in addition to decreasing the potential risk for uncontrolled asthma, will principally prevent individuals from developing asthma and COPD in the future.…”
mentioning
confidence: 99%